Nutritional status, prognostic nutritional index, and preoperative nutritional support as prognostic factors in clinical outcome of gastrointestinal cancer patients. - Taslim, Nurpudji Astuti; Tombilayuk, Grace M; Dianasanti, Margaretha; As’ad, Suryani; Bukhari, Agussalim; Rasyid, Haerani A; Syauki, A Yasmin; Prihantono, Prihantono (Nutrición Clínica y Dietética Hospitalaria, 2023)
Cancer patients are at risk for malnutrition. Nutrition screening using Subjective Global Assessment and Prognostic Nutritional Index (PNI) was associated with postoperative outcomes. Preoperative nutrition support should be given before patient undergo elective surgery. This study aims to find the relationship between nutritional status, PNI, duration of preoperative nutritional support to clinical outcome of gastrointestinal cancer patients, which are postoperative complications and length of stay. This is a cross-sectional study of 72 eligible subjects of 132 participants with gastrointestinal cancer who underwent surgery and met the research criteria, using medical records data. Moderate malnutrition was observed to be higher with preoperative PNI values less than 35. There was no significant relationship between nutritional status, PNI, duration of preoperative nutritional support on the incidence of infection and surgical complications and total length of stay of postoperative gastrointestinal cancer patients. In conclusion, there was no significant correlation between 3 variables with the incidence postoperative complications and total length of hospital stay, but there was a significant relationship between the duration of preoperative nutritional support and the postoperative length of hospital stay in patients with gastrointestinal cancer.